Decoding social media speak: developing a speech act theory research agenda. Issue 2 (21st March 2016) - Ludwig, Stephan; de Ruyter, Ko
Abstract : Purpose: – Drawing on the theoretical domain of speech act theory (SAT) and a discussion of its suitability for setting the agenda for social media research, this study aims to explore a range of research directions that are both relevant and conceptually robust, to stimulate the advancement of knowledge and understanding of online verbatim data. Design/methodology/approach: – Examining previously published cross-disciplinary research, the study identifies how recent conceptual and empirical advances in SAT may further guide the development of text analytics in a social media context. Findings: – Decoding content and function word use in customers' social media communication can enhance the efficiency of determining potential impacts of customer reviews, sentiment strength, the quality of contributions in social media, customers' socialization perceptions in online communities and deceptive messages. Originality/value: – Considering the variety of managerial demand, increasing and diverging social media formats, expanding archives, rapid development of software tools and fast-paced market changes, this study provides an urgently needed, theory-driven, coherent research agenda to guide the conceptual development of text analytics in a social media context.